1995
DOI: 10.1105/tpc.7.10.1583
|View full text |Cite
|
Sign up to set email alerts
|

Male and female flowers of the dioecious plant sorrel show different patterns of MADS box gene expression.

Abstract: Male and female flowers of the dioecious plant sorrel (Rumex acetosa) each produce three whorls of developed floral organs: two similar whorls of three perianth segments and either six stamens (in the male) or a gynoecium consisting of a fertile carpel and two sterile carpels (in the female). In the developing male flower, there is no significant proliferation of cells in the center of the flower, in the position normally occupied by the carpels of a hermaphrodite plant. In the female flower, small stamen prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(47 citation statements)
references
References 16 publications
1
46
0
Order By: Relevance
“…In the hexamerous flower the sepals are arranged in two whorls of three and often become differentiated morphologically, especially at fruiting, closely resembling a trimerous flower (Ronse De Craene 2010). Ainsworth et al (1995) found no B-gene expression in the perianth of Rumex, but confuse petals with sepals in suggesting that sepaloidy is the result of a secondary restriction of petaloidy in the 'petals'. However, the flower in Polygonaceae is basically apetalous.…”
Section: Perianth In the Caryophyllalesmentioning
confidence: 93%
See 4 more Smart Citations
“…In the hexamerous flower the sepals are arranged in two whorls of three and often become differentiated morphologically, especially at fruiting, closely resembling a trimerous flower (Ronse De Craene 2010). Ainsworth et al (1995) found no B-gene expression in the perianth of Rumex, but confuse petals with sepals in suggesting that sepaloidy is the result of a secondary restriction of petaloidy in the 'petals'. However, the flower in Polygonaceae is basically apetalous.…”
Section: Perianth In the Caryophyllalesmentioning
confidence: 93%
“…Albert et al 1998, Kramer et al 1998, Lamb & Irish 2003, Ronse De Craene 2007, Rasmussen et al 2009, Irish 2009). These studies have focussed on the canonical ABC(DE) model to explain the molecular control of floral organ identities.…”
Section: Towards a Molecular Definition Of The Petal?mentioning
confidence: 93%
See 3 more Smart Citations